Peer Relationship Contribution - Ode Yahyu Herliany Yusuf; Nur Susi Saltifa; Karni Karni; Wa Aya; Anriati Anriati; Nur Aysa (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Education is an effort to help the souls of students, both born and mental, from their nature towards a better human civilization. Likewise, peer groups are social environments where members interact where members have the same age, besides that members also have similar schools, hobbies, interests, social status, economics, and so on. The purpose of this study is to find out how a teacher builds interaction and social competence of children with their peers. Because nowadays, there are rampant conflicts between children and peers such as bullying both in the classroom and outside the classroom. So that with this research, it will make it easier for teachers to regulate the classroom climate and social climate when the learning process takes place for children and their peers.